2019
DOI: 10.1021/acs.nanolett.9b00187
|View full text |Cite
|
Sign up to set email alerts
|

Plasmon-Based Biofilm Inhibition on Surgical Implants

Abstract: The insertion of an implant in the body of a patient raises the risk of a posterior infection and formation of a biofilm, which can have critical consequences on the patient’s health and be associated with a high sanitary cost. While antibacterial agents can be used to prevent the infection, such a strategy is time-limited and causes bacteria resistance. As an alternative to biochemical approaches, we propose here to use light-induced local hyperthermia with plasmonic nanoparticles. This strategy is implemente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 29 publications
0
49
0
Order By: Relevance
“…Interestingly, recent studies have demonstrated the formation of ROS at the surface of metallic nanoparticles (6365). For example, LSPR-based antibacterial treatment with gold nanoparticles has been reported (6668).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, recent studies have demonstrated the formation of ROS at the surface of metallic nanoparticles (6365). For example, LSPR-based antibacterial treatment with gold nanoparticles has been reported (6668).…”
Section: Resultsmentioning
confidence: 99%
“…In their clinically relevant investigations on the ZnO‐SQ coated titanium sheets, 48 h incubation with S. aureus culture was carried out. There was a remarkable presence of proliferating biofilms before light treatment; however, 70% biomass reduction could be obtained when the sheet was illuminated under red light for 1 h, suggesting disruption of biofilms due to photoinduced ROS generation by ZnO‐SQ 157. This is foreseen as a promising strategy to be used as antibacterial coatings for superficial or dental implants.…”
Section: Nanomaterial‐integrated Diagnosis Prevention and Therapy Omentioning
confidence: 99%
“…These compounds or materials could sensitize biofilm infections to conventional antibiotics [6,37]. In addition, photosensitizers and plasmonic nanoparticles were used in combination with lasers to eradicate the biofilm via photodynamic and photothermal therapy [38][39][40][41][42][43]. Extracellular polysaccharides are the major component of biofilm matrix [44].…”
Section: Introductionmentioning
confidence: 99%